The influence of BRCA1's ubiquitin ligase activity on cell motility - Sengupta, S (2014)
Breast cancer type 1 susceptibility protein (BRCA1) has been established as an important tumour suppressor protein and its loss of function is associated with hereditary breast and ovarian cancer. An emerging body of work suggests that BRCA1 is involved in sporadic cases of breast and ovarian cancers and may also have a role in other cancers, indicating a more global role in tumourigenesis. BRCA1-mutated cancers can be early-onset and are characterised by being highly aggressive with a propensity to metastasize, thus from a clinical perspective there is a requirement to understand the molecular mechanisms in order to be able to tailor treatments and develop therapeutics. BRCA1 has numerous cellular functions, many ascribed to its role in maintenance of genome integrity, transcription and checkpoint control. More recently, a number of extra-nuclear roles have been established. An interesting novel function is the role of the E3 ubiquitin ligase activity on cell motility. Abrogation of the ubiquitin ligase activity of BRCA1 results in cells exhibiting a hypermotile, invasive phenotype which may help to account for the metastatic nature of BRCA1-mutated tumours. Our aim was to further elucidate BRCA1’s role in cell motility, starting with the identification of relevant candidate ubiquitin ligase substrates. To date, there has yet to be a systematic approach to identify BRCA1’s ubiquitin ligase substrates. Thus we undertook an unbiased proteomic approach to identify extra-nuclear candidates by comparing the profiles of ubiquitinated proteins in breast cancer epithelial cells expressing either functional BRCA1 or ubiquitin ligase-dead BRCA1. We identified 55 candidates which were differentially enriched between the two cell lines and through pathway analysis we determined a significant proportion were cytoskeletal and translation related proteins. Using an ubiquitin-remnant profiling approach, we also identified the site(s) of ubiquitination for many of the candidates. To assess the role of these candidates in cell motility initially we adopted an in silico approach. We used existing time-lapse movies from the online database (www.mitocheck.org) which systematically siRNA knocked down every single gene in the human genome. We developed a series of algorithms which track cell motility from these movies and used these to analyse 192,000 movies containing 3.5 billion cell steps. We have produced a complete database containing motility information after siRNA knockdown of every gene in the human genome, which has been annotated with gene ontologies, KEGG families, Gene Descriptions, SwissProt, Ensembl IDs and siRNA information. In addition to providing motility data of our candidates, we also carried out gene set enrichment analysis on the whole dataset to uncover structural or functional families that may be involved in up-regulating motility when knocked down by siRNA. This is the first report of a genome-wide motility database. Based on overlaps between the results from these two large-scale unbiased proteomic and in silico datasets, we selected 4 candidates, namely, ezrin, moesin, fermitin-2 and delta-catenin. Through monolayer wound healing, cell spreading and single cell motility assays, we determined that ezrin was a particularly relevant and informative candidate. The hypermotile phenotype observed in cells expressing ubiquitin ligase dead BRCA1 was rescued through siRNA knockdown of ezrin and thus we suggest that BRCA1 may regulate cell motility through effects on ezrin. This thesis has investigated candidate BRCA1’s role in cell motility, identified candidate substrates for the E3 ubiquitin ligase activity, established a genome-wide motility database and proposed a possible pathway through which BRCA1 may mediate cell motility and by extension metastasis.